The gateway of remote sensing practices into urban and regional planning in Malaysia - Hj. Mohd. Noor, Norzailawati (2011)
Remote sensing have been applied in many areas of study such as agriculture, forestry, marine, geology, environment including urban planning.However in Malaysia, remote sensing tools have been practiced in certain areas such forestry and agricultural.Urban planning in Malaysia still find the tune to capture the availability and potential provided by remote sensing imagery.